Evaluasi Kesiapan Fisik Calon Jamaah Haji Kabupaten Bungo Melalui Pengukuran VO₂MAX dan Indeks Massa Tubuh - Desi Metriana Erza; Yessy Fitriani; Icha Wieke Firnanda; Gustian Dwi Jayanti (Jurnal Medika: Medika, 2026)
The Hajj pilgrimage is a form of worship that demands high physical readiness, as pilgrims must perform strenuous and repetitive activities over long durations under challenging environmental conditions. However, many prospective Hajj pilgrims, particularly the elderly, have health and fitness statuses that are not yet optimal. This community service activity aimed to evaluate the physical readiness of prospective Hajj pilgrims in Bungo Regency through measurements of Body Mass Index (BMI) and aerobic capacity (VO₂max) as indicators of nutritional status and cardiorespiratory fitness. The methods used included measurements of height and body weight to calculate BMI, as well as fitness testing using the Rockport method supported by the SIPGAR application. The activity involved 148 prospective Hajj pilgrims and was conducted in a structured manner, starting from socialization, physical examinations, fitness testing, to the provision of health education. The results showed that only 42.7% of participants had a normal BMI, while 51.3% were overweight and the remaining 4.7% were classified as underweight. In addition, participants’ VO₂max results indicated that 15.3% were in the good category, 60.7% in the moderate category, and 22.7% in the poor and very poor categories. These findings indicate a relationship between non-ideal BMI and low aerobic capacity, which may potentially hinder the performance of Hajj rituals. This activity underscores the importance of planned fitness evaluation and intervention, as well as improvements in nutritional status, as efforts to enhance the physical readiness of prospective Hajj pilgrims.